World economic outlook : a survey by the staff of the International Monetary Fund. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1980)
The World Economic Outlook (WEO) presents the IMF staff's analysis and projections of economic developments at the global level, in major country groups (classified by region, stage of development, etc.), and in many individual countries. It focuses on major economic policy issues as well as on the analysis of economic developments and prospects. It is usually prepared twice a year, as documentation for meetings of the International Monetary and Financial Committee, and forms the main instrument of the IMF's global surveillance activities.
Some issues have also unique subtitles.
oif 21/05/2013, rpm 12/09/2013, osa 09/10/2013
Reference
Keywords: Economic forecasting; Economic conditions; Economic history; Economic development; Economic policy; International economic relations